The Association of Telangiectasias with Other Peripheral Vascular Lesions of Systemic Sclerosis - Bobeica C; Niculet E; Musat CL; Iancu L; Craescu M; Luca AM; Stefanescu BI; Gheorghe E; Debita M; Vasile CI; Balan G; Busila C; et al. (Dove Medical Press, 2024)
Carmen Bobeica,1,* Elena Niculet,2,3,* Carmina Liana Musat,2,* Lina Iancu,4 Mihaela Craescu,2,3 Andreea Mioara Luca,5 Bogdan Ioan Stefanescu,6 Emma Gheorghe,7 Mihaela Debita,8 Claudiu-Ionut Vasile,8 Gabriela Balan,8- 10 Camelia Busila,8 Alin Laurentiu Tatu3,8,11 1Medical Department, Faculty of Medicine and Pharmacy, "Dunărea de Jos" University, Galați, 800008, Romania; 2Department of Morphological and Functional Sciences, Faculty of Medicine and Pharmacy, "Dunărea de Jos" University, Galați, 800008, Romania; 3Multidisciplinary Integrated Center of Dermatological Interface Research MIC-DIR (Centrul Integrat Multidisciplinar de Cercetare de Interfata Dermatologica - CIM-CID), "Dunărea de Jos" University, Galați, Romania; 4Faculty of Medicine and Pharmacy, "Dunărea de Jos" University, Galați, 800008, Romania; 5Department of Plastic Surgery, "Sf. Ioan" Clinical Emergency Hospital for Children, Galați, 800487, Romania; 6Clinical Surgical Department, Faculty of Medicine and Pharmacy, "Dunărea de Jos" University, Galați, Romania; 7Department No. 1 (Preclinical), Faculty of Medicine and Pharmacy, "Ovidius" University, Constanța, 900527, Romania; 8Clinical Medical Department, Faculty of Medicine and Pharmacy, "Dunărea de Jos" University, Galați, 800008, Romania; 9Department of Gastroenterology, "Sf. Apostol Andrei" County Emergency Clinical Hospital, Galaţi, 800578, Romania; 10Research Center in the Field of Medical and Pharmaceutical Sciences, "Dunărea de Jos" University, Galaţi, 800008, Romania; 11Dermatology Department, "Sf. Cuvioasa Parascheva" Clinical Hospital of Infectious Diseases, Galați, 800179, Romania*These authors contributed equally to this workCorrespondence: Elena Niculet; Carmina Liana Musat, Department of Morphological and Functional Sciences, Faculty of Medicine and Pharmacy, "Dunărea de Jos" University of Galați, 35 Alexandru Ioan Cuza Street, Galați, 800216, Romania, Tel +40741398895 ; +40723338438, Email helena_badiu@yahoo.com; carmina.musat@ugal.roPurpose: Systemic sclerosis (SSc) is a relatively rare collagenosis manifested as microvasculopathy, excessive cutaneous and visceral fibrosis in a background of autoimmune alteration. Autoimmune vasculopathy in SSc occurs early and begins with endothelial cell activation followed by blood vessel intimal proliferation in a context of defective angiogenesis. The alteration of peripheral micro and macrocirculation in SSc is evident through vascular lesions, such as Raynaud's phenomenon, telangiectasias, acrocyanosis, digital ulcers, gangrene, peripheral pulse deficiency. Our paper details the results of the study on the association between telangiectasias and other types of immune-mediated peripheral vascular lesions that can be identified in SSc. The presence of these peripheral vascular lesions can provide information about the magnitude of the peripheral vasculopathy.Patients and Methods: A total of 37 patients diagnosed with SSc, recruited from a university clinic in Bucharest between February 2019 and March 2020, were enrolled in an observational study. We evaluated the presence of telangiectasias, as a stigma of autoimmune microvasculopathy, and their association with other immune-mediated peripheral vascular lesions that may be present in SSc.Results: The presence of telangiectasias was identified in the absence, but especially in the presence of acrocyanosis and digital ulcerations, and patients with peripheral pulse deficiency almost always had telangiectasias. Less than a quarter of the patients with digital ulcers progressed unfavorably to gangrene, and only one required amputation, telangiectasias being present not only in the patient with amputation but in all patients with gangrene.Conclusion: We appreciate that telangiectasias may be the clinical expression of peripheral vasculopathy characteristic of SSc, they can often be present in association with other peripheral vascular lesions and may represent a valuable indicator for the gangrene risk of digital ulcerations in SSc.Keywords: systemic sclerosis, vascular lesions, phenomenon Raynaud's, telangiectasias, acrocianosis, digital ulcers